Evaluation of four new studies on the potential toxicity of titanium dioxide used as a food additive (E 171). (4th July 2018) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Dusemund, Birgit; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; et al.
Abstract: The European Commission requested EFSA to carry out a scientific evaluation on four studies on the potential toxicity of titanium dioxide (TiO2 ) used as a food additive (E 171) and to indicate whether they would merit re‐opening the existing opinion of EFSA on the safety of TiO2 (E 171) as a food additive. The results of the Bettini et al. (2017 ) study did not provide enough justification for a new carcinogenicity study, but, should additional useful mechanistic information become available, this could be reconsidered in future. The new in vitro findings in the Proquin et al. (2017 ) study did not modify the conclusion on the genotoxicity of TiO2 as stated in the previous EFSA opinion of 2016 on the safety of TiO2 (E 171) as a food additive. The effects of engineered TiO2 nanoparticles reported by the Guo et al. (2017 ) study were of uncertain biological significance and therefore of limited relevance for the risk assessment of the food additive TiO2 (E 171). There was significant uncertainty in the risk assessment performed by Heringa et al. (2016 ), which did not include a weight of evidence analysis of the whole database. The Panel considered that the four studies evaluated, highlighted some concerns but with uncertainties, therefore their relevance for the risk assessment was considered limited and further research would be needed to decrease the level of uncertainties. Overall, three of the studies, reporting that TiO2 induced various effects in in vitro and in vivo models, may be useful for hazard identification of TiO2 . In the fourth study by Heringa et al. (2016 ), numerous assumptions were made, which resulted in large uncertainty in their conclusion. Altogether, the Panel concluded that the outcome of the four studies did not merit re‐opening the existing opinion of EFSA related to the safety of TiO2 (E 171) as a food additive.